Highly Concentrated Nitrogen‐Doped Carbon Nanotubes in Alginate–Gelatin 3D Hydrogels Enable in Vitro Breast Cancer Spheroid Formation. Issue 3 (19th December 2021) - Munguia-Lopez, Jose G.; Jiang, Tao; Ferlatte, Audrey; Fajardo-Diaz, Juan L.; Munoz-Sandoval, Emilio; Tran, Simon D.; Kinsella, Joseph M.
Abstract : Carbon nanotubes' (CNTs) physicochemical and mechanical properties make them ideal reinforcement materials for hydrogels, but distributing CNTs homogeneously in hydrogels remains a challenge. Chemical modifications to CNTs are used to facilitate nanomaterial dispersion, thus improving hydrogels' physicochemical properties. Among CNTs, nitrogen‐doped CNTs (CN x ) possess both great dispersibility in solution and biocompatibility properties. By formulating a method to incorporate CN x within alginate (i.e., covalently grafting alginate to the CN x surface versus noncovalently adsorbing alginate to the CN x surface) creates extrudable materials with tunable physical, chemical, and thermal properties. Herein, three new composites of alginate‐CN x are created. The results indicate that all composites present different physicochemical and thermal properties, suggesting that alginate is reorganized according to their degree of oxidation. These composites show cytocompatibility with MDA‐MB‐231 and regulation over the size of spheroids formed within the matrix. CN x within the matrix negatively affects MCF‐7 cells viability, spheroid formation rate, and the quantity of spheroids developed during culture. These materials provide a useful 3D hydrogel that can be used to develop in vitro models to understand the role of microenvironmental factors such as stiffness or surface roughness on the development of spheroids and their subsequent phenotypic behavior. Abstract : Oxidized alginate chains covalently grafting to the surface of nitrogen‐doped carbon nanotubes are reorganized based upon the oxidation degree and show different thermal properties. The new composites control the size and formation of MDA‐MB‐231 breast cancer spheroids without affecting their viability, while nanomaterial‐containing hydrogels affect both viability and spheroid formation of MCF‐7 cells.